Effects of carbohydrate use on preoperative thirst: a randomized clinical trial - Carla Brandão de Oliveira; Aline Korki Arrabal Garcia; Leonel Alves do Nascimento; Marília Ferrari Conchon; Rejane Kiyomi Furuya; Renne Rodrigues; Ligia Fahl Fonseca (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to evaluate the effectiveness of carbohydrate popsicles, carbohydrate solution, and usual care (fasting) on the intensity and discomfort of preoperative thirst. Methods: a randomized clinical trial with 60 preoperative patients aged between 18 and 60 years, randomized into three groups: control (fasting), carbohydrate solution (100 ml), and carbohydrate popsicle (100 ml). The outcomes were thirst intensity and discomfort. Results: there was a difference between groups for final thirst intensity (p = 0.01) and final thirst discomfort (p = 0.001). The effect size for both the Solution Group and the Popsicle Group was robust: 0.99 and 1.14, respectively. Conclusions: the groups that received the carbohydrate fasting abbreviation showed a reduction in thirst discomfort compared to the control group. The carbohydrate popsicle proved more effective in reducing the intensity of thirst. NCT: 3.209.283